Field scale water-use efficiency inherent variability and options for crop selection and management - Richter G.M.; Lawlor D.; Latiri K.; Acutis M.; Qureshi K. (WEMED workshop: how to advance the knowledge on water use efficiency in the Mediterranean region ?, 2007)
Rising atmospheric (CO2) can increase photosynthesis and yield of crops, but rising temperature could increase transpiration more strongly. Water-use efficiency (WUE, total dry matter or yield produced per unit of water used) is the result of these two intensely intertwined processes. WUE is therefore implicitly variable due to effects of climatic/environmental variation, management and crop properties, which sheds some doubt on its usefulness. In a classical field experiment for spring barely using a rain-shelter, WUE in 1979 differed from that of a drier year (1976) due to the difference in vapour pressure deficit (VPD). We present results using an improved photosynthesis based crop model describing meteorological and biophysical processes in various climates, simulating growth, yield and water use. For typical field conditions in the UK, temporal variability of WUE was greater than spatial variability. The model can also quantify the effects of management, e.g. sowing date. A sensitivity analysis ranks the importance of the model's crop parameters according to environment. Sowing date was the most sensitive management decision to achieve large yields. In the Mediterranean (Tunisia), parameters for the establishment (early vigour) of Durum wheat were the most important factors for increasing production and using water most efficiently. Overall, WUE was an indicator less sensitive than yield and it seems that focus on WUE obscures the relevance of yield determining factors.
Workshop on: How to Advance the Knowledge on Water Use Efficiency in the Mediterranean Region ? 2006/10/26-28, Valenzano (Italy)